Landmarks for endoscopic approach to the parapharyngeal internal carotid artery: A radiographic and cadaveric study. (10th June 2014) - Ho, Brian; Jang, David W.; Van Rompaey, Jason; Figueroa, Ramon; Brown, Jimmy J.; Carrau, Ricardo L.; Solares, C. Arturo
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To define transnasal endoscopic surgical landmarks for the parapharyngeal segment of the internal carotid artery (ppICA) using radiographic analysis and cadaveric dissection. Study Design Cadaveric and radiographic study. Methods One hundred seventy‐nine computed tomography angiography studies of the head and neck were analyzed using Osirix third‐party software (Pixmeo, Geneva, Switzerland). Dissection of a cadaveric specimen was used as a correlate to radiographic findings. The posterior aspect of the lateral pterygoid process and posterior border of the mandibular ramus were used as bony landmarks for the ppICA. Results At the level of the nasal floor, the distance from the ppICA to the posterolateral pterygoid process and to the posterior mandibular ramus was 2.36 cm and 1.94 cm, respectively, in males, and 2.37 cm and 1.99 cm, respectively, in females. At the level of the skull base, the distance from the ppICA to the posterolateral pterygoid process and to the posterior mandible was 2.33 cm and 1.49 cm, respectively, in males, and 2.20 cm and 1.57 cm, respectively, in females. Cadaver dissection demonstrated the utility of identifying these landmarks. Conclusions The posterior border of the mandibular ramus and the posterolateral aspect of the pterygoid process may serve as consistent bony landmarks for identification of the ppICA. Level of Evidence NA Laryngoscope, 124:1995–2001, 2014